A project of the highest national importance: Welfare and psy-scientific discourses in the Leros institutions - Karydaki, Danae (Neusis, 2024)
During the period of national reconstruction that followed the Greek Civil War, the victorious side, and especially the state of the “nation-minded” and the royal couple of Paul and Federica, employed the welfare policy for the children and people with physical, intellectual, and mental disabilities as a means towards the domination of the ideology of “nation-mindedness”. Due to the former Italian military infrastructure, three applications of welfare policy emerged on the island of Leros: the Royal Schools (1949-1964), the mental hospital (1957) and the first PIKPA asylum for “incurable children” (1961). Through the study of these institutions’ archival material, legislation, Athenian and local Press as well as oral testimonies, this paper maps the ways in which the psy-scientific discourse and the welfare policy discourse are intertwined with “nation-minded” ideology in the case of the Leros institutions.